IMPACT OF SOCIAL MEDIA PLATFORMS ON FARMERS’ LIVELIHOOD ASSETS IN NORTH-WESTERN NIGERIA - Muhammad, Ahmad; Ango, A. K.; Barau, A. A. (FUDMA JOURNAL OF SCIENCES, 2025)
This study assessed the impact of Social media on farmers livelihood assets in North-western Nigeria. A multi-stage sampling technique was used to select 369 respondents that constitute the sample size of the study. Data used for the study were collected with the aid of a structured questionnaire which was analysed using Principal component analysis, a descriptive and inferential statistics tool. Results of the study revealed that the mean age of the respondents was 40 years, majority of whom were male (80%) and married (84%) with an average household size of 6 people. Most of the farmers (71%) had low level of education and the mean annual income and the average farm size were N928188.00 and 2.01 hectares respectively. Results further indicated that 22% of the farmers Off-farm livelihood activities was being middlemen while, cereal farming (37%) and goat and sheep farming (68%) were more prominent On-farm livelihood activities engaged by the farmers. WhatsApp (90%) and Facebook (92%) were the leading Social media platforms used by the farmers. Majority of the farmers (84%) used social media platforms daily and majority (89%) used the platforms on hourly basis, also, 42% of them were lower social media users. Thus social media has a significant impact on the farmers livelihood. Hence farmers should be encouraged to explore all online avenues to access extension services that could improve their livelihoods.